Hashimoto's Thyroiditis and Entero-Chromaffin-like Cell Hyperplasia: Early Detection and Somatostatin Analogue Treatment. (September 2013) - Renzullo, A.; Accardo, G.; Esposito, D.; De Bellis, A.; Bizzarro, A.; Romano, M.; Federico, A.; Gravina, A.G.; Conzo, G.; Pannone, G.; Faggiano, A.; Colao, A.; et al.
Type IIIb polyglandular autoimmune disease comprises autoimmune thyroid disease (HT) and chronic atrophic gastritis (AIG). Hypergastrinemia, secondary to AIG, predisposes to gastric enterochromaffin-like cell (ECL) hyperplasia, a preneoplastic condition. We evaluated the prevalence of AIG, hypergastrinemia and ECL hyperplasia in HT patients. A secondary end-point was to assess the efficacy of treatment with a somatostatin analogue in HT patient with ECL hyperplasia. From 2009 to 2011, 146 HT patients were enrolled in a prospective study. All cases underwent hormonal profile, and parietal cell antibody (PCA), gastrin, and chromogranin A (CgA) serum level assays. Selected patients with elevated gastrin and CgA levels underwent gastro esophageal endoscopy (EGDS). Patients positive for ECL hyperplasia received Octreotide LAR 30 mg/28 days for 12 months. Gastrin and CgA assays were repeated every three months and EGDS after one year. The results show that gastrin and CgA were significantly higher than normal in 17/115 (14.7%) patients. Seven more HT had isolated PCA positivity and in the 17 PCA positive patients histology diagnosed AIG, corpus prevalent, with mild to moderate atrophy. Diffuse ECL hyperplasia of the gastric body was present in three subjects, one of them presenting a type-1 carcinoid. Gastrin and CgA levels were significantly reduced (p<0.01) after 3 months of therapy with a somatostatin analogue and returned to normal after 1 year. ECL hyperplasia regressed in all three patients. We suggest that selected HT patients may need a more accurate surveillance for early signs of gastric EC risk. In the case of altered values of gastrin and in the presence of PCA positivity, EGDS and histology should be performed for an early diagnosis of AIG and treatment of ECL hyperplasia.